Positive electrode active material for non-aqueous electrolyte storage element, positive electrode for non-aqueous electrolyte storage element, non-aqueous electrolyte storage element, storage device, method for using non-aqueous electrolyte storage element, and method for manufacturing non-aqueous electrolyte storage element

A lithium transition metal composite oxide with aluminum, nickel, and manganese, and controlled oxygen position parameter, addresses the need for improved charge/discharge cycle capacity retention and high rate discharge characteristics in non-aqueous electrolyte storage devices, enhancing their performance.

JP7601091B2Active Publication Date: 2024-12-17GS YUASA CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022514378
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-04-07
Filing Date
2021-03-23
Publication Date
2024-12-17
Estimated Expiration
2041-03-23

AI Technical Summary

Technical Problem

Non-aqueous electrolyte storage devices require improvements in charge/discharge cycle capacity retention rate and high rate discharge characteristics.

Method used

A positive electrode active material for non-aqueous electrolyte storage devices containing a lithium transition metal composite oxide with aluminum, nickel, and manganese, with controlled oxygen position parameter and specific potential ranges, is developed to enhance charge/discharge cycle capacity retention and high rate discharge characteristics.

Benefits of technology

The proposed active material improves charge/discharge cycle capacity retention and high rate discharge characteristics by controlling the oxygen position parameter and potential, resulting in enhanced performance of non-aqueous electrolyte storage elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601091000002
    Figure 0007601091000002
  • Figure 0007601091000003
    Figure 0007601091000003
  • Figure 0007601091000001
    Figure 0007601091000001
Patent Text Reader

Abstract

A positive electrode active material for non-aqueous electrolyte electricity storage elements according to one aspect of the present invention comprises a lithium transition metal composite oxide having an α-NaFeO2 structure and further contains aluminum, in which the lithium transition metal composite oxide contains at least one of nickel and cobalt and also contains manganese, the molar content ratio of manganese in transition metals in the lithium transition metal composite oxide is 0.6 or less, and the oxygen positional parameter of the positive electrode active material is 0.265 to 0.269, inclusive, in which the oxygen positional parameter is determined from a crystal structure analysis by Rietveld method using a space group R3-m in a crystal structure model on the basis of an X-ray diffraction pattern in a charged state at a potential of 4.35 V vs. Li / Li+ without such a charge history that the potential does not reach 4.5 V vs. Li / Li+ or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode active material for a nonaqueous electrolyte storage element, a positive electrode for a nonaqueous electrolyte storage element, a nonaqueous electrolyte storage element, an electricity storage device, a method for using a nonaqueous electrolyte storage element, and a method for producing a nonaqueous electrolyte storage element. [Background technology]

[0002] The use of non-aqueous electrolyte storage elements, such as lithium secondary batteries, has expanded in recent years, and there is a demand for the development of various positive electrode active materials. Conventionally, lithium transition metal composite oxides having an α-NaFeO2 type crystal structure have been considered as positive electrode active materials for non-aqueous electrolyte storage elements, and LiCoO2 and LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 Non-aqueous electrolyte secondary batteries using so-called LiMeO2 type active materials, such as LiMeO2, have been put to practical use. In the LiMeO2 type active material, the molar ratio of lithium to transition metal (Li / Me) constituting the lithium transition metal composite oxide is approximately 1.

[0003] Meanwhile, in recent years, so-called lithium-excess active materials have been developed among lithium transition metal composite oxides having an α-NaFeO2 crystal structure, in which the molar ratio of lithium to transition metal (Li / Me) exceeds 1 (Patent Documents 1 and 2). Non-aqueous electrolyte storage elements using such lithium-excess active materials have attracted attention because they have a larger discharge capacity than LiMeO2 active materials.

[0004] Patent Document 1 describes a positive electrode active material in which an Al oxide is added to the particle surface of a lithium transition metal composite oxide. Patent Document 1 also describes that the oxygen position parameter of the lithium transition metal composite oxide, which is determined by crystal structure analysis by the Rietveld method based on the X-ray diffraction pattern at the end of charging after a history of constant current and constant voltage charging at a voltage of 4.6 V, is preferably 0.267 or more.

[0005] Patent Document 2 describes a positive electrode active material made of a composite oxide powder formed by mixing Co, Al-containing β-type nickel oxyhydroxide with lithium hydroxide monohydrate, heat-treating the mixed powder, and pulverizing it. Patent Document 2 also describes that the oxygen position parameter of this composite oxide powder, which is determined by crystal structure analysis using the Rietveld method, is preferably 0.2360 or more and 0.2420 or less. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2016-167446 A [Patent Document 2] JP 2002-124261 A Summary of the Invention [Problem to be solved by the invention]

[0007] In non-aqueous electrolyte electricity storage elements, there is a demand for further improvements in charge / discharge cycle capacity retention rate and high rate discharge characteristics.

[0008] The present invention aims to provide a positive electrode active material for a nonaqueous electrolyte storage element, which is capable of improving the charge / discharge cycle capacity retention rate and high-rate discharge characteristics, a positive electrode for a nonaqueous electrolyte storage element, a nonaqueous electrolyte storage element, an electricity storage device, and a method for using and a method for manufacturing the nonaqueous electrolyte storage element. [Means for solving the problem]

[0009] One aspect of the present invention is a positive electrode active material for a non-aqueous electrolyte storage element, which contains a lithium transition metal composite oxide having an α-NaFeO2 structure, further containing aluminum, the lithium transition metal composite oxide containing at least one of nickel and cobalt, and manganese, the content of manganese in the transition metal in the lithium transition metal composite oxide being 0.6 or less in molar ratio, and the potential being 4.5 V vs. Li / Li +Potential of 4.35V vs. Li / Li without any charging history + In the positive electrode active material (A) for a nonaqueous electrolyte storage element, an oxygen position parameter of the positive electrode active material, which is determined by crystal structure analysis by the Rietveld method using the space group R3-m as a crystal structure model based on an X-ray diffraction pattern in a charged state of 0.265 or more and 0.269 or less.

[0010] Another aspect of the present invention is a positive electrode active material for a non-aqueous electrolyte storage element, which contains a lithium transition metal composite oxide having an α-NaFeO2 structure, further containing aluminum, and the lithium transition metal composite oxide contains at least one of nickel and cobalt, and manganese, and has a potential of 4.5 V vs. Li / Li + Potential of 4.35V vs. Li / Li without any charging history + and a positive electrode active material (B) for a nonaqueous electrolyte storage element, wherein the absolute value of the difference between an oxygen position parameter of the positive electrode active material obtained by crystal structure analysis by the Rietveld method when space group R3-m is used as a crystal structure model based on an X-ray diffraction pattern in a charged state of 0.002 or less and an oxygen position parameter obtained by the crystal structure analysis of a positive electrode active material which does not contain aluminum and has the same molar ratio of transition metal elements as the positive electrode active material.

[0011] Another aspect of the present invention is a positive electrode for a nonaqueous electrolyte storage element, comprising either the positive electrode active material (A) or the positive electrode active material (B).

[0012] Another embodiment of the present invention is a nonaqueous electrolyte electricity storage element including the positive electrode for the nonaqueous electrolyte electricity storage element.

[0013] Another embodiment of the present invention is an electricity storage device including a plurality of nonaqueous electrolyte electricity storage elements, the electricity storage device including at least one of the nonaqueous electrolyte electricity storage elements.

[0014] In another embodiment of the present invention, the positive electrode potential is 4.5 V vs. Li / Li + and charging the nonaqueous electrolyte storage element within a range of less than 100%.

[0015] In another embodiment of the present invention, the positive electrode potential is 4.5 V vs. Li / Li + The method for producing a nonaqueous electrolyte storage element includes performing initial charging and discharging within a range of less than 100%. Effect of the Invention

[0016] According to one aspect of the present invention, it is possible to provide a positive electrode active material for a nonaqueous electrolyte storage element, a positive electrode for a nonaqueous electrolyte storage element, a nonaqueous electrolyte storage element, an electricity storage device, and a method of using and a method of manufacturing the nonaqueous electrolyte storage element, which are capable of improving the charge-discharge cycle capacity retention rate and high-rate discharge characteristics. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is an external perspective view showing a nonaqueous electrolyte electricity storage element according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing an electricity storage device formed by assembling a plurality of nonaqueous electrolyte electricity storage elements according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] First, an outline of the positive electrode active material for a nonaqueous electrolyte storage element, the positive electrode for a nonaqueous electrolyte storage element, the nonaqueous electrolyte storage element, the electricity storage device, and the method of using and the method of manufacturing the nonaqueous electrolyte storage element disclosed in this specification will be described.

[0019] A positive electrode active material (A) for a non-aqueous electrolyte storage element according to one embodiment of the present invention is a positive electrode active material for a non-aqueous electrolyte storage element containing a lithium transition metal composite oxide having an α-NaFeO2 structure, further containing aluminum, the lithium transition metal composite oxide containing at least one of nickel and cobalt, and manganese, the content of manganese in the transition metal in the lithium transition metal composite oxide being 0.6 or less in molar ratio, and a potential of 4.5 V vs. Li / Li + Potential of 4.35V vs. Li / Li without any charging history +In the charged state, the oxygen position parameter of the positive electrode active material obtained by crystal structure analysis by the Rietveld method using the space group R3-m as a crystal structure model based on the X-ray diffraction pattern is 0.265 or more and 0.269 or less.

[0020] The positive electrode active material (A) for a non-aqueous electrolyte storage element has a potential of 4.5 V vs. Li / Li + Potential of 4.35V vs. Li / Li without any charging history + By controlling the oxygen position parameter in the charged state within the above range, the oxygen position parameter can be made substantially the same as the oxygen position parameter in the charged state of a positive electrode active material having a composition that does not contain aluminum and has the same molar ratio of the transition metal elements contained therein. Furthermore, since the manganese content in the transition metals of the positive electrode active material for a nonaqueous electrolyte storage element is equal to or less than the above upper limit, the charge / discharge cycle capacity retention rate of the nonaqueous electrolyte storage element can be increased. Therefore, the positive electrode active material for a nonaqueous electrolyte storage element can easily increase the charge / discharge cycle capacity retention rate and high rate discharge characteristics of the nonaqueous electrolyte storage element.

[0021] A positive electrode active material (B) for a non-aqueous electrolyte storage element according to another embodiment of the present invention is a positive electrode active material for a non-aqueous electrolyte storage element, which contains a lithium transition metal composite oxide having an α-NaFeO2 structure, and further contains aluminum. The lithium transition metal composite oxide contains at least one of nickel and cobalt, and manganese, and has a potential of 4.5 V vs. Li / Li + Potential of 4.35V vs. Li / Li without any charging history + In a charged state of the positive electrode active material, the absolute value of the difference between an oxygen position parameter of the positive electrode active material obtained by crystal structure analysis by the Rietveld method when the space group R3-m is used as a crystal structure model based on an X-ray diffraction pattern and an oxygen position parameter obtained by the crystal structure analysis of a positive electrode active material which does not contain aluminum and has the same molar ratio of transition metal elements as the positive electrode active material is 0.002 or less.

[0022] In this specification, the composition ratio of the lithium transition metal composite oxide refers to the composition ratio when the element is fully discharged by the following method. First, the nonaqueous electrolyte storage element is charged at a constant current of 0.05 C until the end-of-charge voltage in normal use is reached, and the element is fully charged. After a 30-minute break, the element is discharged at a constant current of 0.05 C until the lower limit voltage in normal use is reached. The element is disassembled, the positive electrode is removed, and the positive electrode is then cut into 1 to 10 cm 2 The positive electrode is cut out to a sufficiently small area of ​​about 100 mm. A test battery is assembled using this positive electrode with a metallic lithium electrode as the counter electrode, and a constant current discharge is performed at a current value of 10 mA per 1 g of positive electrode mixture until the terminal voltage becomes 2.0 V, adjusting the positive electrode to a fully discharged state. For composition analysis, the battery is disassembled again and the positive electrode is taken out. The non-aqueous electrolyte attached to the taken-out positive electrode is thoroughly washed using dimethyl carbonate, and the positive electrode mixture is dried at room temperature for a day and night, and then peeled off from the positive electrode substrate and collected for measurement. The work from disassembling the non-aqueous electrolyte storage element to collecting the positive electrode mixture is performed in an argon atmosphere with a dew point of -60°C or less. Here, normal use refers to the case where the non-aqueous electrolyte storage element is used by adopting the charge and discharge conditions recommended or specified for the non-aqueous electrolyte storage element, and if a charger for the non-aqueous electrolyte storage element is prepared, the charger is applied to use the non-aqueous electrolyte storage element.

[0023] In the present specification, the oxygen position parameter is measured by the following procedure. First, the nonaqueous electrolyte storage element is charged at a constant current of 0.05 C until the end-of-charge voltage in normal use is reached, and the element is fully charged. After a 30-minute break, the element is discharged at a constant current of 0.05 C until the lower limit voltage in normal use is reached. The element is then disassembled, the positive electrode is removed, and the positive electrode is then inserted into a 1 to 10 cm 2Cut out a piece of the positive electrode with a sufficiently small area of ​​about 1000 μm. Using this positive electrode, a test battery is assembled with a metallic lithium electrode as the counter electrode, and a constant current discharge is performed at a current value of 10 mA per 1 g of positive electrode mixture until the terminal voltage reaches 2.0 V, adjusting the positive electrode to a fully discharged state. Next, a constant current constant voltage charge is performed with a charging current of 1.0 C and a charge cut-off voltage of 4.35 V. Since the counter electrode is metallic lithium in this case, the potential of the metallic lithium counter electrode in an open circuit state is approximately equal to the redox potential of lithium, so when the charge cut-off voltage of the test battery is 4.35 V, the positive electrode reachable potential is 4.35 V vs. Li / Li. + In this charged state, the positive electrode is taken out in a dry room, and without cleaning, the mixture peeled off from the positive electrode substrate is crushed in a mortar and subjected to X-ray diffraction measurement. Crystal structure analysis is performed by the Rietveld method for all diffraction lines except for the peaks due to the metallic aluminum used as the positive electrode substrate. The program used for Rietveld analysis is RIETAN-2000 (Izumi et al., Mat. Sci. Forum, 321-324, 198 (2000)). The profile function used in the analysis is the pseudo-Voigt function of TCH. The peak position shift parameters are refined in advance using a silicon standard sample (Nist 640c) with known lattice constants. The crystal structure model of the positive electrode active material is set to the space group R3-m, and the following parameters are refined at each atomic position. Background Parameters Lattice constant Oxygen Position Parameter Gaussian function half-width parameter Half-width parameter of the Lorentz function Asymmetric parameters Preferred orientation parameters Isotropic atomic displacement parameters (Li atoms are fixed at 0.75) The actual data is refined using diffraction data between 15 and 85° (CuKα) until the S value, which indicates the difference with the crystal structure model, falls below 1.3. This refinement performs background processing, and based on the results of subtracting the background, the peak intensity values ​​and half-width values ​​of each diffraction line can be obtained.

[0024] As a result of extensive research by the present inventors, it was found that in a positive electrode active material for a non-aqueous electrolyte storage element containing aluminum, the potential is 4.5 V vs. Li / Li + Potential of 4.35V vs. Li / Li without any charging history + It has been found that by controlling the oxygen position parameter in the charged state of the positive electrode active material (A) or (B), it is possible to improve both the charge / discharge cycle capacity retention rate and the high-rate discharge characteristics of a nonaqueous electrolyte storage element comprising the positive electrode active material (A) or (B) for a nonaqueous electrolyte storage element. In other words, it has been found that the positive electrode active material (A) or (B) for a nonaqueous electrolyte storage element can improve both the charge / discharge cycle capacity retention rate and the high-rate discharge characteristics of a nonaqueous electrolyte storage element when the oxygen position parameter in the charged state is approximately the same as the oxygen position parameter in the charged state of a positive electrode active material that does not contain aluminum and has the same molar ratio of transition metal elements contained therein. It is considered that the oxygen position parameter of the positive electrode active material (A) or (B) for a nonaqueous electrolyte storage element can be controlled to a desired range by, for example, dissolving a part of aluminum in the lithium transition metal composite oxide while having another part of aluminum present on the surface of the lithium transition metal composite oxide.

[0025] In the positive electrode active material (B) for non-aqueous electrolyte storage element, the content of manganese in the transition metal in the lithium transition metal composite oxide is preferably 0.3 to 0.7 in terms of molar ratio. In this way, by setting the content of manganese in the transition metal in the lithium transition metal composite oxide within the above range, the charge-discharge cycle capacity retention rate of the non-aqueous electrolyte storage element including the positive electrode active material (B) for non-aqueous electrolyte storage element can be increased. In addition, in general, when a lithium transition metal composite oxide containing such a relatively high content of manganese is used, the internal resistance is likely to increase due to the elution of manganese. In contrast, since the positive electrode active material (B) for non-aqueous electrolyte storage element contains aluminum, even if it contains manganese in the above range, the increase in internal resistance due to charge-discharge cycles is sufficiently suppressed.

[0026] The ratio of the number of moles of lithium to the number of moles of transition metal in the lithium transition metal composite oxide is preferably from 1.0 to 1.4. By setting the ratio of the number of moles of lithium to the number of moles of transition metal in the lithium transition metal composite oxide within the above range, the charge / discharge cycle capacity retention rate of the nonaqueous electrolyte storage element can be increased while the discharge capacity of the nonaqueous electrolyte storage element can be increased.

[0027] The positive electrode active material (A) or (B) for a nonaqueous electrolyte storage element may have a ratio of the number of moles of aluminum to the number of moles of transition metal in the lithium transition metal composite oxide of 0.1 or more and 2 or less. This configuration makes it easy to control the oxygen position parameter within a desired range. Therefore, it is easy to improve the charge / discharge cycle capacity retention rate and high rate discharge characteristics.

[0028] The positive electrode active material (A) or (B) for non-aqueous electrolyte storage element is a particle containing the lithium transition metal composite oxide, and the ratio of the number of moles of aluminum to the sum of the number of moles of transition metal and the number of moles of aluminum is preferably larger near the surface than near the center of the particle. In this way, the ratio of the number of moles of aluminum to the sum of the number of moles of transition metal and the number of moles of aluminum is larger near the surface than near the center of the particle, so that the oxygen position parameter can be reliably controlled within a desired range. Therefore, the charge-discharge cycle capacity retention rate and high-rate discharge characteristics can be more easily and reliably improved.

[0029] A positive electrode for a nonaqueous electrolyte storage element according to another embodiment of the present invention includes either the positive electrode active material (A) or the positive electrode active material (B).

[0030] The positive electrode for a nonaqueous electrolyte storage element includes either the positive electrode active material (A) or the positive electrode active material (B), and therefore can improve the charge / discharge cycle capacity retention rate and high rate discharge characteristics.

[0031] A nonaqueous electrolyte electricity storage element according to another embodiment of the present invention includes the positive electrode for the nonaqueous electrolyte electricity storage element.

[0032] The nonaqueous electrolyte storage element includes the positive electrode for a nonaqueous electrolyte storage element, and therefore can improve the charge / discharge cycle capacity retention rate and high rate discharge characteristics.

[0033] A power storage device according to another embodiment of the present invention includes a plurality of nonaqueous electrolyte power storage elements, and includes at least one of the nonaqueous electrolyte power storage elements.

[0034] The non-electrical storage device includes one or more non-aqueous electrolyte electric storage elements, and therefore can improve the charge / discharge cycle capacity retention rate and high rate discharge characteristics.

[0035] The positive electrode potential at the end of charge voltage during normal use of the nonaqueous electrolyte storage element is 4.5 V vs. Li / Li + It is preferable that the positive electrode potential at the end-of-charge voltage during normal use of the nonaqueous electrolyte storage element is within the above range. It is presumed that the lithium transition metal composite oxide is gradually activated with many repeated charge / discharge cycles, and the lithium ions released from the lithium transition metal composite oxide during charge / discharge gradually increase (hereinafter, the "gradual activation of the lithium transition metal composite oxide with repeated charge / discharge cycles during use" is also referred to as "aging"). As a result, it is possible to replenish the lithium ions consumed by the formation of a coating film on the negative electrode during charge / discharge cycles from the lithium transition metal composite oxide on the positive electrode, and it is considered that the charge / discharge cycle capacity retention rate can be easily increased.

[0036] A method of using a nonaqueous electrolyte storage element according to another embodiment of the present invention is to + It is equipped with charging range of less than.

[0037] According to this method of use, it is possible to improve the charge / discharge cycle capacity retention rate and the high rate discharge characteristics.

[0038] In another embodiment of the present invention, a method for producing a nonaqueous electrolyte storage element is provided. +It is equipped with an initial charge / discharge range of less than

[0039] According to this production method, a nonaqueous electrolyte electricity storage element having excellent charge / discharge cycle capacity retention rate and high rate discharge characteristics can be produced.

[0040] In the present invention, the expression "the ratio of the number of moles of aluminum to the sum of the number of moles of transition metal and the number of moles of aluminum is higher near the surface than near the center of the particle" means that the ratio in the region including the surface of the positive electrode active material for a nonaqueous electrolyte storage element is higher than the ratio in the region including the center of the particle containing a lithium transition metal composite oxide. The ratio can be obtained by measuring the metal composition ratio from the surface of the particle to the center of the particle using a scanning electron microscope (SEM) and an energy dispersive X-ray analyzer (EDX) as described in paragraphs 0088 to 0089 of Japanese Patent No. 5871186. Here, the distance from the center of the particle to the surface of the particle is divided into eight equal parts, and each region is set as a measurement point. The center of the particle is set as Point 0, and the outermost surface of the particle is set as Point 8. The "near the center" and the "near the surface" refer to the region of Point 0 and the region of Point 8, respectively.

[0041] Hereinafter, a positive electrode active material for a nonaqueous electrolyte storage element, a positive electrode for a nonaqueous electrolyte storage element, a nonaqueous electrolyte storage element, an electricity storage device, a method for using a nonaqueous electrolyte storage element, and a method for manufacturing a nonaqueous electrolyte storage element according to one embodiment of the present invention will be described. Note that in this embodiment, the nonaqueous electrolyte storage element is a nonaqueous electrolyte secondary battery (hereinafter, also simply referred to as a "secondary battery").

[0042] <Positive electrode active material for non-aqueous electrolyte storage element> The positive electrode active material for a non-aqueous electrolyte storage element (hereinafter, also simply referred to as "the positive electrode active material") contains a lithium transition metal composite oxide having an α-NaFeO2 structure. The positive electrode active material is a particle containing the lithium transition metal composite oxide. The positive electrode active material further contains aluminum. The lithium transition metal composite oxide contains at least one of nickel and cobalt, and manganese. It is preferable that the positive electrode active material does not contain any metal element other than aluminum, lithium, and transition metals. Note that "the positive electrode active material does not contain any metal element other than aluminum, lithium, and transition metals" means that the content of metal elements other than aluminum, lithium, and transition metals in the positive electrode active material is 0.1 mass% or less, preferably 0.01 mass% or less.

[0043] The positive electrode active material has a potential of 4.5V vs. Li / Li + Potential of 4.35V vs. Li / Li without any charging history + In the charged state of the battery, the oxygen position parameter (zO1) obtained from crystal structure analysis by the Rietveld method when the space group R3-m is used as a crystal structure model based on the X-ray diffraction pattern satisfies at least one of the following conditions (1) and (2): (1) The oxygen position parameter (zO1) is 0.265 or more and 0.269 or less. (2) The absolute value of the difference between the oxygen position parameter (zO1) and the oxygen position parameter (zO2) determined in the same manner as above for a positive electrode active material that does not contain aluminum and has the same molar ratio of transition metal elements as the positive electrode active material is 0.002 or less.

[0044] The oxygen position parameter is the value of z when the spatial coordinates of the transition metal (Me) are defined as (0,0,0), the spatial coordinates of lithium as (0,0,1 / 2), and the spatial coordinates of oxygen as (0,0,z) for the α-NaFeO2 type crystal structure of the lithium transition metal composite oxide belonging to the space group R3-m. In other words, the oxygen position parameter is a relative index indicating how far the oxygen position is from the transition metal position.

[0045] By satisfying the condition (1), the positive electrode active material (A) can make the oxygen position parameter (zO1) substantially equal to the oxygen position parameter (zO2). This allows the positive electrode active material to improve the charge / discharge cycle capacity retention rate and high-rate discharge characteristics of the storage element. The lower limit of the oxygen position parameter (zO1) is preferably 0.266. The upper limit of the oxygen position parameter (zO1) is preferably 0.268.

[0046] The positive electrode active material (B) can improve both the charge / discharge cycle capacity retention rate and the high-rate discharge characteristics of a nonaqueous electrolyte storage element (hereinafter, simply referred to as the "storage element") including the positive electrode active material by satisfying the above condition (2). When the above condition (2) is satisfied, the oxygen position parameter (zO2) is preferably the oxygen position parameter of a positive electrode active material having the same ratio of the number of moles of lithium to the number of moles of transition metal as that of the positive electrode active material. The upper limit of the absolute value of the difference between the oxygen position parameter (zO1) and the oxygen position parameter (zO2) is preferably 0.001. It is considered that the oxygen position parameter (zO1) of the positive electrode active material can be controlled to be substantially the same as the oxygen position parameter (zO2) by, for example, dissolving a part of aluminum in the lithium transition metal composite oxide while having another part of aluminum present on the surface of the lithium transition metal composite oxide.

[0047] The transition metal content (mol) is X Me , the manganese (Mn) content (mol) is X Mn In this case, the Mn content (X Mn / X Me The upper limit of the content (X) is preferably 0.7, more preferably 0.6, and even more preferably 0.55. In particular, when the positive electrode active material satisfies the above condition (2), Mn / X Me The upper limit of the content (X) is preferably 0.6. Mn / X Me) to be equal to or less than the upper limit, the charge / discharge cycle capacity retention rate of the energy storage element can be increased.

[0048] The positive electrode active material (B) is suitable for improving the charge-discharge cycle capacity retention rate and high-rate discharge characteristics of the storage element when a lithium transition metal composite oxide containing a relatively high content of manganese is used. The Mn content (X Mn / X Me The lower limit of the content (X) is preferably 0.1, more preferably 0.3, and even more preferably 0.4. Mn / X Me By making the content of the polymerizable compound (A) equal to or more than the lower limit, the effect of chemical conversion over time is enhanced, and the charge-discharge cycle capacity retention rate can be increased.

[0049] Nickel (Ni) content (mol) x Ni In this case, the Ni content (X Ni / X Me The lower limit of the content (X) may be, for example, 0, preferably 0.1, more preferably 0.2, and even more preferably 0.3. Ni / X Me The upper limit of the content (X) may be, for example, 0.7, preferably 0.6, and more preferably 0.5. Ni / X Me By making the content (X ) equal to or greater than the lower limit, it is possible to improve the output performance, energy density, etc. Ni / X Me ) to be equal to or less than the upper limit, the charge / discharge cycle capacity retention rate can be increased.

[0050] Cobalt (Co) content (mol) x Co In this case, the content of Co in the transition metal (Me) in the lithium transition metal composite oxide (X Co / X Me The lower limit of the content (X) may be, for example, 0, and preferably 0.1. Co / XMe The upper limit of the content (X) may be, for example, 0.6, and preferably 0.3. Co / X Me By making the content (X ) equal to or greater than the lower limit, the output performance, energy density, etc. can be improved. Co / X Me ) to be equal to or less than the above upper limit, it is possible to suppress the raw material cost while exhibiting a sufficient charge / discharge cycle capacity retention rate.

[0051] Lithium (Li) content (mol) x Li In this case, the ratio of the number of moles of lithium (Li) to the number of moles of transition metal (Me) in the lithium transition metal composite oxide (X Li / X Me The lower limit of the ratio (X) may be, for example, 1.0, preferably more than 1.0, more preferably 1.05, and even more preferably 1.1. Li / X Me The upper limit of the ratio (X ) is preferably 1.5, more preferably 1.4, and even more preferably 1.3. In particular, when the above-mentioned condition (2) is satisfied, the above ratio (X Li / X Me The upper limit of the above ratio (X) is preferably 1.3. Li / X Me By making the ratio (X ) within the above range, the charge / discharge cycle capacity retention rate of the energy storage element can be increased and the discharge capacity can be increased. Li / X Me ) exceeds 1.0, the active material is configured as a so-called lithium-excess type active material.

[0052] Aluminum increases the charge / discharge cycle capacity retention rate of the energy storage element. The form in which aluminum is present is not particularly limited, and aluminum may be dissolved in the lithium transition metal composite oxide, or may be present as a component separate from the lithium transition metal composite oxide. However, in the positive electrode active material, it is preferable that a part of aluminum is dissolved in the lithium transition metal composite oxide, and another part is present on the surface of the lithium transition metal composite oxide as a component separate from the lithium transition metal composite oxide.

[0053] When a part of aluminum is dissolved in the lithium transition metal composite oxide, the lithium transition metal composite oxide may be, for example, Li 1+α (Ni β Co γ Mn δ Al ε ) 1-α It may be represented as O2 (0<α<1, 0≦β<1, 0≦γ<1, 0<δ<1, 0<ε<1, β+γ+δ+ε=1, β+γ≠0).

[0054] The aluminum (Al) content (mol) in the positive electrode active material is X Al In this case, the ratio of the number of moles of aluminum (Al) to the number of moles of the transition metal (Me) in the entire positive electrode active material (X Al / X Me The lower limit of the ratio (X) is preferably 0.02, and more preferably 0.05. Al / X Me The upper limit of the above ratio (X) is preferably 2.5, more preferably 1.7. Al / X Me By setting zO1 within the above range, it is easy to control the oxygen position parameter (zO1) within the above desired range. Therefore, the charge-discharge cycle capacity retention rate and high-rate discharge characteristics of the energy storage element can be easily and reliably improved.

[0055] In the positive electrode active material, the ratio of the number of moles of aluminum (Al) to the sum of the number of moles of the transition metal (Me) and the number of moles of aluminum (Al) is preferably larger near the surface of the particle containing the lithium transition metal composite oxide than near the center of the particle. As described above, a part of aluminum (Al) is dissolved in the lithium transition metal composite oxide, and another part of aluminum (Al) is present on the surface of the particle containing the lithium transition metal composite oxide, so that the ratio near the surface of the particle can be made larger than the ratio near the center of the particle. The positive electrode active material can increase the charge / discharge cycle capacity retention rate of the storage element by increasing the ratio near the surface of the particle containing the lithium transition metal composite oxide. On the other hand, if the ratio near the surface of the particle becomes too large, the positive electrode active material will cause a decrease in high-rate discharge characteristics. In this respect, the storage element can sufficiently increase the charge / discharge cycle capacity retention rate while maintaining high-rate discharge characteristics by dispersing aluminum inside and outside the particle containing the lithium transition metal composite oxide.

[0056] Here, the aluminum content in the positive electrode active material is a value measured by ICP (inductively coupled plasma) atomic emission spectrometry.

[0057] The lithium transition metal composite oxide may contain other metal elements, etc., as long as the effects of the present invention are achieved, and may be mixed with other metal elements, etc., as impurities. When the lithium transition metal composite oxide contains other metal elements, the oxygen position parameter (zO2) is preferably the oxygen position parameter of a positive electrode active material having the same ratio of the number of moles of the other metal elements to the number of moles of the transition metal as that of the positive electrode active material.

[0058] The positive electrode active material may contain other positive electrode active materials other than the lithium transition metal composite oxide. The other positive electrode active materials can be appropriately selected from known positive electrode active materials that are usually used in lithium ion secondary batteries and the like. As the other positive electrode active materials, materials capable of absorbing and releasing lithium ions are usually used. For example, the above-mentioned LiMeO2 type active material, lithium transition metal oxides having a spinel crystal structure, polyanion compounds, chalcogen compounds, sulfur, etc. can be mentioned. However, the content of the lithium transition metal composite oxide in the total positive electrode active material contained in the positive electrode active material is preferably 80 mass% or more, more preferably 90 mass% or more, even more preferably 99 mass% or more, and even more preferably 100 mass%.

[0059] The average particle size of the positive electrode active material is preferably, for example, 0.1 μm or more and 20 μm or less. By setting the average particle size of the positive electrode active material to the above lower limit or more, the positive electrode active material can be easily manufactured or handled. By setting the average particle size of the positive electrode active material to the above upper limit or less, the electronic conductivity of the positive electrode active material layer is improved. Here, the "average particle size" refers to a value at which the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50% based on the particle size distribution measured by a laser diffraction / scattering method for a diluted solution obtained by diluting particles with a solvent in accordance with JIS-Z-8825 (2013).

[0060] (Method of manufacturing positive electrode active material) Examples of the manufacturing method of the positive electrode active material (positive electrode active material particles) include (1) a method of immersing a particulate positive electrode active material in a liquid in which an aluminum compound (a compound containing aluminum) is dissolved or suspended, followed by drying, (2) a method of immersing a particulate positive electrode active material in a liquid in which an aluminum compound is dissolved or suspended, followed by reacting by heating or the like, (3) a method of firing a mixture containing a positive electrode active material precursor, a lithium compound, and an aluminum compound, (4) a method of firing a mixture containing an aluminum compound and a particulate positive electrode active material, and (5) a method of firing a mixture containing an aluminum-containing positive electrode active material precursor and a lithium compound. Among these, (5) the method of firing a mixture containing an aluminum-containing positive electrode active material precursor and a lithium compound is preferred. By manufacturing the positive electrode active material by such a method, it is easy to make a part of the aluminum solid-solve in the lithium transition metal composite oxide, while making the other part of the aluminum present on the surface of the lithium transition metal composite oxide. In particular, the positive electrode active material is prepared by producing a positive electrode active material precursor by dropping an aqueous solution containing nickel, cobalt, manganese, etc. and an aqueous solution containing aluminum into water in a reaction tank and mixing them separately, and then calcining a mixture containing this positive electrode active material precursor and a lithium compound, thereby adjusting the amount of aluminum dissolved in the lithium transition metal composite oxide and making it easy to appropriately control the oxygen position parameter (zO1). Below, a detailed description will be given of a method for producing a positive electrode active material according to the above method (5).

[0061] The positive electrode active material precursor is preferably a coprecipitated precursor in which nickel, cobalt, manganese, aluminum, or the like is present in one particle.

[0062] The co-precursor is prepared by using a reactive crystallization method. Here, examples of the co-precipitation precursor include hydroxide precursors and carbonate precursors. Here, in the method for producing a carbonate precursor, the crystallization rate is high and it is difficult to control the amount of aluminum dissolved in the solid solution, whereas in the method for producing a hydroxide precursor, the crystallization rate can be easily controlled by applying a complexing agent, making it easy to adjust the amount of aluminum dissolved in the solid solution. From this viewpoint, the method for producing a hydroxide precursor is preferable from the viewpoint of adjusting the amount of aluminum dissolved in the lithium transition metal composite oxide.

[0063] When producing the hydroxide precursor, it is preferable to add an aqueous alkali solution containing an alkali metal hydroxide (neutralizing agent), a complexing agent, and a reducing agent to the water (aqueous solution) in a reaction tank that is kept alkaline, together with an aqueous solution containing a transition metal (Me) and aluminum, to co-precipitate the transition metal hydroxide and aluminum hydroxide. As the complexing agent, ammonia (NH3), ammonium sulfate, ammonium nitrate, etc. can be used. As the reducing agent, hydrazine, sodium borohydride, etc. can be used. As the alkali metal hydroxide, sodium hydroxide, lithium hydroxide, potassium hydroxide, etc. can be used.

[0064] When producing the carbonate precursor, it is preferable to add an aqueous alkali solution containing a neutralizing agent such as sodium carbonate or lithium carbonate, and a complexing agent together with an aqueous solution containing a transition metal (Me) and aluminum to water (aqueous solution) in a reaction tank maintained alkaline, thereby coprecipitating the transition metal carbonate and aluminum carbonate.

[0065] Regarding the raw materials of the precursor, Ni compounds include nickel hydroxide, nickel carbonate, nickel sulfate, nickel nitrate, nickel acetate, etc. Co compounds include cobalt sulfate, cobalt nitrate, cobalt acetate, etc. Mn compounds include manganese oxide, manganese carbonate, manganese sulfate, manganese nitrate, manganese acetate, etc.

[0066] In preparing the precursor, Mn is easily oxidized, so it is not easy to prepare a precursor in which Ni, Co and Mn are uniformly distributed in a divalent state, and the uniform mixing of Ni, Co and Mn at the atomic level is likely to be insufficient. Therefore, in order to suppress the oxidation of Mn present in the precursor, it is preferable to remove the dissolved oxygen in water or an aqueous solution. As a method for removing the dissolved oxygen, a method of bubbling with a gas that does not contain oxygen can be mentioned. Examples of the gas that does not contain oxygen include, but are not limited to, nitrogen gas, argon gas, carbon dioxide gas, and the like.

[0067] It is preferable to drop the aqueous solution containing the transition metal (Me) and the aqueous solution containing Al separately. According to this method, it is difficult to uniformly disperse Al in the transition metal (Me). More specifically, it is difficult to uniformly mix the transition metal hydroxide and the aluminum hydroxide. As a result, it is easy to adjust the amount of aluminum dissolved in the lithium transition metal composite oxide. The pH of the aqueous solution and the dropping speed of the aqueous solution when preparing the precursor in the aqueous solution are not particularly limited, and conditions similar to those of the conventionally known manufacturing conditions can be adopted. The pH of the aqueous solution can be, for example, 8 to 11, and may be 9.5 to 10.5. The dropping speed of the aqueous solution can be, for example, 0.1 cm 3 / min or more 10cm 3 / min or less.

[0068] When a complexing agent such as NH3 is present in the reaction vessel and certain convection conditions are applied, continuing stirring after the end of the drop of the raw solution promotes the rotation of the particles and their revolution in the stirring vessel, during which the particles collide with each other and grow stepwise into concentric spheres. In other words, the coprecipitation precursor is formed through a two-step reaction: a metal complex formation reaction when the raw solution is dropped into the reaction vessel, and a precipitation formation reaction that occurs while the metal complex is retained in the reaction vessel.

[0069] The preferred duration of stirring after the dropwise addition of the raw material aqueous solution, i.e., the reaction time, is influenced by the size of the reaction vessel, stirring conditions, pH, reaction temperature, etc., but is preferably, for example, from 0.5 hours to 20 hours, and more preferably from 1 hour to 15 hours.

[0070] The precursor (positive electrode active material precursor) obtained by the above method is mixed with a Li compound and fired to obtain positive electrode active material particles. As the Li compound, lithium hydroxide, lithium carbonate, etc. can be used. In addition to these Li compounds, LiF, Li2SO4, or Li3PO4 can be used as a sintering aid. The addition ratio of these sintering aids is preferably 1 to 10 mol% based on the total amount of Li compounds. In addition, the total amount of Li compounds is preferably about 1 to 5 mol% in excess, in anticipation of the loss of some of the Li compounds during firing.

[0071] The sintering temperature is preferably 750° C. or more and 1,000° C. or less. By setting the sintering temperature to the above lower limit or more, it is possible to obtain positive electrode active material particles with a high degree of sintering, and to improve the charge-discharge cycle performance. On the other hand, by setting the sintering temperature to the above upper limit or less, it is possible to suppress the deterioration of discharge performance due to the structural change from the layered α-NaFeO2 structure to the rock salt type cubic structure.

[0072] In order to obtain particles such as positive electrode active material particles in a predetermined shape, a pulverizer, a classifier, etc. are used. Examples of the pulverization method include a method using a mortar, a ball mill, a sand mill, a vibration ball mill, a planetary ball mill, a jet mill, a counter jet mill, a swirling airflow type jet mill, or a sieve. When pulverizing, wet pulverization in which water or an organic solvent such as hexane is present can also be used. As a classification method, a sieve, a wind classifier, etc. are used as necessary for both dry and wet methods.

[0073] <Positive electrode for non-aqueous electrolyte storage element> The positive electrode for a storage element (hereinafter, simply referred to as "the positive electrode") has a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or via an intermediate layer. The positive electrode active material layer contains the positive electrode active material. Since the positive electrode includes the positive electrode active material, it is possible to improve the charge / discharge cycle capacity retention rate and high-rate discharge characteristics.

[0074] The positive electrode substrate has electrical conductivity. "Conductivity" means that the volume resistivity measured in accordance with JIS-H-0505 (1975) is 10 7 "Non-conductive" means that the volume resistivity is 10 7 It means that the resistance is more than Ω·cm. As the material of the positive electrode substrate, metals such as aluminum, titanium, tantalum, stainless steel, etc. or alloys thereof are used. Among these, aluminum or aluminum alloys are preferred from the viewpoints of potential resistance, high conductivity, and cost. As the positive electrode substrate, foil, vapor deposition film, etc. can be mentioned, and foil is preferred from the viewpoint of cost. Therefore, aluminum foil or aluminum alloy foil is preferred as the positive electrode substrate. Examples of aluminum or aluminum alloys include A1085, A3003, etc. specified in JIS-H-4000 (2014).

[0075] The average thickness of the positive electrode substrate is preferably 5 μm or more and 50 μm or less, more preferably 10 μm or more and 40 μm or less. By setting the average thickness of the positive electrode substrate to the above lower limit or more, the strength of the positive electrode substrate can be increased. By setting the average thickness of the positive electrode substrate to the above upper limit or less, the energy density per volume of the secondary battery can be increased. The "average thickness" of the substrate refers to the value obtained by dividing the punched mass when a substrate of a predetermined area is punched out by the true density and punched area of ​​the substrate. The "average thickness" of the negative electrode substrate described later is defined in the same manner.

[0076] The intermediate layer is a layer disposed between the positive electrode substrate and the positive electrode active material layer. The configuration of the intermediate layer is not particularly limited, and includes, for example, a resin binder and conductive particles. The intermediate layer includes, for example, conductive particles such as carbon particles, thereby reducing the contact resistance between the positive electrode substrate and the positive electrode active material layer.

[0077] The positive electrode active material layer is a layer of a positive electrode mixture containing the positive electrode active material. The positive electrode active material layer (positive electrode mixture) may contain optional components such as a conductive agent, a binder, a thickener, and a filler as necessary in addition to the positive electrode active material.

[0078] The content of the positive electrode active material in the positive electrode active material layer (positive electrode mixture) is preferably 70% by mass to 98% by mass, more preferably 80% by mass to 97% by mass, and even more preferably 90% by mass to 96% by mass. By setting the content of the positive electrode active material in the above range, the electric capacity of the secondary battery can be increased.

[0079] The conductive agent is not particularly limited as long as it is a material having electrical conductivity. Examples of such conductive agents include graphite; carbon black such as furnace black and acetylene black; metals; and conductive ceramics. The conductive agent may be in the form of powder or fiber. Among these, acetylene black is preferred from the viewpoint of electronic conductivity and coatability.

[0080] The content of the conductive agent in the positive electrode active material layer (positive electrode mixture) is preferably 1% by mass or more and 10% by mass or less, and more preferably 2% by mass or more and 5% by mass or less. By setting the content of the conductive agent in the above range, the electric capacity of the secondary battery can be increased.

[0081] Examples of binders include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.

[0082] The content of the binder in the positive electrode active material layer (positive electrode mixture) is preferably 1% by mass to 10% by mass, more preferably 2% by mass to 5% by mass. By setting the binder content within the above range, the active material can be stably held.

[0083] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC), methyl cellulose, etc. When the thickener has a functional group that reacts with lithium or the like, this functional group may be deactivated in advance by methylation or the like.

[0084] The filler is not particularly limited, and examples of the filler include polyolefins such as polypropylene and polyethylene, silica, alumina, zeolite, glass, and alumina silicate.

[0085] The positive electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material particles, conductive agent, binder, thickener, and filler.

[0086] <Non-aqueous electrolyte electricity storage element> The storage element has the positive electrode described above, a negative electrode, and a non-aqueous electrolyte. The positive electrode and the negative electrode are usually stacked or wound with a separator between them to form an electrode body. The electrode body is housed in a container, and the container is filled with a non-aqueous electrolyte. The non-aqueous electrolyte is interposed between the positive electrode and the negative electrode. In addition, as the container, a commonly used known metal container, resin container, or the like can be used. Since the storage element has the positive electrode, it is possible to improve the charge / discharge cycle capacity retention rate and high-rate discharge characteristics.

[0087] (Negative electrode) The negative electrode has a negative electrode substrate and a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer. The configuration of the intermediate layer of the negative electrode is not particularly limited and may be the same as that of the intermediate layer of the positive electrode.

[0088] The negative electrode substrate has electrical conductivity. Metals such as copper, nickel, stainless steel, nickel-plated steel, and aluminum, or alloys thereof, are used as the material of the negative electrode substrate. Among these, copper or copper alloys are preferred. Examples of the negative electrode substrate include foils and vapor-deposited films, and foils are preferred from the viewpoint of cost. Therefore, copper foil or copper alloy foil is preferred as the negative electrode substrate. Examples of copper foil include rolled copper foil and electrolytic copper foil.

[0089] The average thickness of the negative electrode substrate is preferably 3 μm or more and 30 μm or less, more preferably 5 μm or more and 20 μm or less. By making the average thickness of the negative electrode substrate equal to or more than the lower limit, the strength of the negative electrode substrate can be increased. By making the average thickness of the negative electrode substrate equal to or less than the upper limit, the energy density per volume of the secondary battery can be increased.

[0090] The negative electrode active material layer is a layer of a negative electrode mixture containing a negative electrode active material. The negative electrode active material layer (negative electrode mixture) may contain optional components such as a conductive agent, a binder, a thickener, and a filler, as necessary, in addition to the negative electrode active material. The optional components such as the conductive agent, the binder, the thickener, and the filler can be the same as those in the positive electrode active material layer. The content of each of these optional components in the negative electrode active material layer can be within the range described as the content of each of these components in the positive electrode active material layer.

[0091] The negative electrode active material can be appropriately selected from known negative electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the negative electrode active material for lithium ion secondary batteries. Examples of the negative electrode active material include metal Li; metals or semimetals such as Si and Sn; metal oxides or semimetal oxides such as Si oxide, Ti oxide, and Sn oxide; Li4Ti5O 12 , LiTiO 2、 Examples of the material include titanium-containing oxides such as TiNb2O7, polyphosphate compounds, silicon carbide, and carbon materials such as graphite and non-graphitic carbon (easily graphitizable carbon or non-graphitizable carbon). In the negative electrode active material layer, one of these materials may be used alone, or two or more of them may be used in combination.

[0092] "Graphite" refers to a material that has an average lattice spacing (d 002 ) is 0.33 nm or more and less than 0.34 nm. Examples of graphite include natural graphite and artificial graphite. Artificial graphite is preferred from the viewpoint of availability of materials with stable physical properties.

[0093] "Non-graphitic carbon" refers to carbon that has an average lattice spacing (d 002 ) is 0.34 nm or more and 0.42 nm or less. Examples of non-graphitizable carbon include non-graphitizable carbon and graphitizable carbon. Examples of non-graphitizable carbon include resin-derived materials, petroleum pitch or petroleum pitch-derived materials, petroleum coke or petroleum coke-derived materials, plant-derived materials, and alcohol-derived materials.

[0094] Here, the "discharged state" that defines graphite and non-graphitic carbon refers to a state in which the open circuit voltage is 0.7 V or more in a single-electrode battery using a negative electrode containing a carbon material as a negative electrode active material as a working electrode and metallic Li as a counter electrode. Since the potential of the metallic Li counter electrode in the open circuit state is approximately equal to the redox potential of Li, the open circuit voltage in the single-electrode battery is approximately equal to the potential of the negative electrode containing the carbon material relative to the redox potential of Li. In other words, the open circuit voltage of 0.7 V or more in the single-electrode battery means that lithium ions that can be absorbed and released during charging and discharging are sufficiently released from the carbon material, which is the negative electrode active material.

[0095] "Non-graphitizable carbon" means the above d 002 This refers to carbon materials with a particle size of 0.36 nm or more and 0.42 nm or less.

[0096] "Graphitizable carbon" means the above d 002 This refers to carbon materials with a particle size of 0.34 nm or more and less than 0.36 nm.

[0097] In order to obtain a secondary battery with a high capacity retention rate, the negative electrode active material is preferably a carbon material, more preferably graphite. When a carbon material is used as the negative electrode active material, the content of the carbon material in the total negative electrode active material may be 50 mass% or more, 70 mass% or more, 90 mass% or more, or substantially 100 mass%.

[0098] The negative electrode active material is usually a particle (powder). The average particle size of the negative electrode active material can be, for example, 1 nm or more and 100 μm or less. By setting the average particle size of the negative electrode active material to the above lower limit or more, the negative electrode active material can be easily manufactured or handled. By setting the average particle size of the negative electrode active material to the above upper limit or less, the electronic conductivity of the active material layer is improved. In order to obtain powder with a predetermined particle size, a pulverizer, a classifier, or the like is used. The pulverization method and the powder classification method can be selected, for example, from the methods exemplified for the positive electrode above.

[0099] The content of the negative electrode active material in the negative electrode active material layer (negative electrode mixture) is preferably 60% by mass or more and 99% by mass or less, and more preferably 90% by mass or more and 98% by mass or less. By setting the content of the negative electrode active material in the above range, both high energy density and manufacturability of the negative electrode active material layer can be achieved.

[0100] The negative electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W as components other than the negative electrode active material, conductive agent, binder, thickener, and filler.

[0101] (Separator) The separator can be appropriately selected from known separators. For example, a separator consisting of only a substrate layer, a separator in which a heat-resistant layer containing heat-resistant particles and a binder is formed on one or both surfaces of the substrate layer, etc. can be used as the separator. Examples of the shape of the substrate layer of the separator include woven fabric, nonwoven fabric, and porous resin film. Among these shapes, a porous resin film is preferred from the viewpoint of strength, and a nonwoven fabric is preferred from the viewpoint of non-aqueous electrolyte retention. As the material of the substrate layer of the separator, polyolefins such as polyethylene and polypropylene are preferred from the viewpoint of shutdown function, and polyimide and aramid are preferred from the viewpoint of oxidation decomposition resistance. A material obtained by combining these resins may be used as the substrate layer of the separator.

[0102] The heat-resistant particles contained in the heat-resistant layer preferably have a mass loss of 5% or less when heated from room temperature to 500°C in the atmosphere, and more preferably have a mass loss of 5% or less when heated from room temperature to 800°C in the atmosphere. Examples of materials that have a mass loss of a predetermined amount or less when heated include inorganic compounds. Examples of inorganic compounds include oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate; hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; sparingly soluble ion crystals such as calcium fluoride, barium fluoride, and barium titanate; covalent crystals such as silicon and diamond; mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, and artificial products thereof. As the inorganic compound, these substances may be used alone or in the form of a complex, or two or more of them may be mixed and used. Among these inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate is preferred from the viewpoint of the safety of the secondary battery.

[0103] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and is preferably 20% by volume or more from the viewpoint of discharge performance. Here, "porosity" refers to a volume-based value measured with a mercury porosimeter.

[0104] As the separator, a polymer gel composed of a polymer and a non-aqueous electrolyte may be used. Examples of the polymer include polyacrylonitrile, polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyvinyl acetate, polyvinylpyrrolidone, and polyvinylidene fluoride. The use of the polymer gel has an effect of suppressing leakage. As the separator, the above-mentioned porous resin film or nonwoven fabric may be used in combination with the polymer gel.

[0105] (Non-aqueous electrolyte) The nonaqueous electrolyte may be appropriately selected from known nonaqueous electrolytes. The nonaqueous electrolyte may be a nonaqueous electrolyte solution. The nonaqueous electrolyte solution includes a nonaqueous solvent and an electrolyte salt dissolved in the nonaqueous solvent.

[0106] The non-aqueous solvent can be appropriately selected from known non-aqueous solvents. Examples of the non-aqueous solvent include cyclic carbonates, chain carbonates, carboxylates, phosphates, sulfonates, ethers, amides, and nitriles. The non-aqueous solvent may be a compound in which some of the hydrogen atoms contained in these compounds are replaced with halogen. For example, by using a fluorinated compound (fluorinated cyclic carbonate, fluorinated chain carbonate, etc.), the non-aqueous solvent can be used sufficiently even under conditions in which the positive electrode potential reaches a high potential.

[0107] Examples of cyclic carbonates include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinylethylene carbonate (VEC), chloroethylene carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), styrene carbonate, 1-phenylvinylene carbonate, 1,2-diphenylvinylene carbonate, etc. Among these, EC, PC and FEC are preferred.

[0108] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, methyl trifluoroethyl carbonate (MFEC), bis(trifluoroethyl) carbonate, etc. Among these, EMC and MFEC are preferred.

[0109] As the non-aqueous solvent, it is preferable to use a cyclic carbonate or a chain carbonate, and it is more preferable to use a combination of a cyclic carbonate and a chain carbonate. By using a cyclic carbonate, it is possible to promote dissociation of the electrolyte salt and improve the ionic conductivity of the non-aqueous electrolyte. By using a chain carbonate, it is possible to keep the viscosity of the non-aqueous electrolyte low. When using a cyclic carbonate and a chain carbonate in combination, it is preferable that the volume ratio of the cyclic carbonate to the chain carbonate (cyclic carbonate:chain carbonate) is, for example, in the range of 5:95 to 50:50.

[0110] The electrolyte salt can be appropriately selected from known electrolyte salts. Examples of the electrolyte salt include lithium salts, sodium salts, potassium salts, magnesium salts, onium salts, etc. Among these, lithium salts are preferred.

[0111] Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, and LiN(SO2F)2, and lithium salts having a halogenated hydrocarbon group such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3. Among these, inorganic lithium salts are preferred, and LiPF6 is more preferred.

[0112] The content of the electrolyte salt in the non-aqueous electrolyte is 0.1 mol / dm 3 More than 2.5mol / dm 3 It is preferable that the value is 0.3 mol / dm or less. 3 More than 2.0mol / dm 3 More preferably, it is 0.5 mol / dm or less. 3 More than 1.7mol / dm 3 More preferably, it is 0.7 mol / dm or less. 3 More than 1.5mol / dm 3 By setting the content of the electrolyte salt within the above range, the ionic conductivity of the nonaqueous electrolyte can be increased.

[0113] The non-aqueous electrolyte may contain an additive. Examples of the additive include aromatic compounds such as biphenyl, alkylbiphenyl, terphenyl, partially hydrogenated terphenyl, cyclohexylbenzene, t-butylbenzene, t-amylbenzene, diphenyl ether, and dibenzofuran; partial halides of the above aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; halogenated anisole compounds such as 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, and 3,5-difluoroanisole; succinic anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, cyclohexyl benzene, and cyclohexyl benzene. hexanedicarboxylic anhydride; ethylene sulfite, propylene sulfite, dimethyl sulfite, dimethyl sulfate, ethylene sulfate, sulfolane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiolane, thioanisole, diphenyl disulfide, dipyridinium disulfide, perfluorooctane, tristrimethylsilyl borate, tristrimethylsilyl phosphate, tetrakistrimethylsilyl titanate, etc. These additives may be used alone or in combination of two or more.

[0114] The content of the additive contained in the non-aqueous electrolyte is preferably 0.01% by mass to 10% by mass, more preferably 0.1% by mass to 7% by mass, even more preferably 0.2% by mass to 5% by mass, and particularly preferably 0.3% by mass to 3% by mass. By setting the content of the additive within the above range, it is possible to improve the capacity retention performance or charge / discharge cycle performance after high-temperature storage, and to further improve safety.

[0115] The non-aqueous electrolyte may be a solid electrolyte, or a non-aqueous electrolyte solution and a solid electrolyte may be used in combination.

[0116] The solid electrolyte can be selected from any material that has ion conductivity such as lithium, sodium, calcium, etc., and is solid at room temperature (e.g., 15° C. to 25° C.). Examples of the solid electrolyte include sulfide solid electrolytes, oxide solid electrolytes, oxynitride solid electrolytes, polymer solid electrolytes, etc.

[0117] Examples of sulfide solid electrolytes include Li2S-P2S5, LiI-Li2S-P2S5, and Li 10 Ge-P2S 12 etc.

[0118] (Positive electrode potential at the end of charge voltage during normal use) In the storage element, the positive electrode potential (positive electrode potential) at the end of charge voltage during normal use is not particularly limited, but is preferably 4.5V vs. Li / Li + Less than 4.45V vs. Li / Li is preferable. + Less than 4.4V vs. Li / Li is more preferable. + In some cases, it may be even more preferable to set the positive electrode potential at the end of charge voltage during normal use to the above upper limit or less. By setting the positive electrode potential at the end of charge voltage during normal use to the above upper limit or less, the aging process gradually progresses with many repeated charge and discharge cycles, so that the charge and discharge cycle capacity retention rate can be increased. In addition, this configuration is considered to make it easier to suppress the change in the crystal structure in the direction of decreasing the diffusion rate of lithium ions in the solid phase. Therefore, it is possible to suppress the increase in internal resistance due to charge and discharge cycles.

[0119] In this storage element, the positive electrode potential at the end of charge voltage during normal use is 4.25V vs. Li / Li + Ultra-low voltage is preferred, 4.3V vs. Li / Li + More than 4.35V vs.Li / Li is more preferable. +In some cases, the above may be even more preferable. By setting the positive electrode potential at the end-of-charge voltage during normal use to the above lower limit or higher, the formation over time progresses sufficiently during normal charging, so that the charge-discharge cycle capacity retention rate can be increased. In addition, by setting the positive electrode potential at the end-of-charge voltage during normal use to the above lower limit or higher, the discharge capacity can be increased, and the energy density, output performance, etc. can be improved.

[0120] The positive electrode potential at the end-of-charge voltage during normal use of the energy storage element may be within a range between any of the above upper limits and any of the above lower limits.

[0121] <Method of using non-aqueous electrolyte storage element> The method of using the nonaqueous electrolyte storage element (secondary battery) according to one embodiment of the present invention is not particularly limited, but the following method is preferable. That is, the method of using the storage element is such that the positive electrode potential (positive electrode ultimate potential) is 4.5 V vs. Li / Li + According to the method of use, it is possible to improve the charge-discharge cycle capacity retention rate and the high-rate discharge characteristics. Also, according to the method of use, it is possible to suppress an increase in internal resistance due to the charge-discharge cycle.

[0122] The upper limit of the positive electrode potential (positive electrode potential) in this charging is 4.45V vs.Li / Li + Less than 4.4V vs. Li / Li is more preferable. + In some cases, it may be more preferable to charge the positive electrode potential to less than 4.25 V vs. Li / Li. + Ultra-low voltage is preferred, 4.3V vs. Li / Li + is more preferable, 4.35V vs. Li / Li + may be more preferable.

[0123] This method of use may be the same as the method of use of a conventionally known secondary battery, except that the positive electrode potential (positive electrode ultimate potential) during charging is as described above.

[0124] <Method of Manufacturing Nonaqueous Electrolyte Storage Element> A method for producing a non-aqueous electrolyte storage element (secondary battery) according to one embodiment of the present invention includes assembling a non-charged / discharged non-aqueous electrolyte storage element having a positive electrode, a negative electrode, and a non-aqueous electrolyte, and initially charging and discharging the non-charged / discharged non-aqueous electrolyte storage element. + The initial charge and discharge are performed within a range of less than 100%. The positive electrode contains the above-mentioned positive electrode active material. According to the manufacturing method, a nonaqueous electrolyte storage element excellent in charge / discharge cycle capacity retention rate and high rate discharge characteristics can be manufactured. Furthermore, according to the manufacturing method, a nonaqueous electrolyte storage element in which an increase in internal resistance due to charge / discharge cycles is suppressed can be manufactured.

[0125] In this manufacturing method, the initial charge / discharge is not intended to actively activate the positive electrode active material, but may be performed, for example, to confirm the capacity. That is, the initial charge / discharge is simply the first charge / discharge performed after assembling the uncharged / discharged nonaqueous electrolyte storage element. The number of charge / discharge cycles in the initial charge / discharge may be one or two, or may be three or more.

[0126] The upper limit of the positive electrode potential (positive electrode potential) during initial charge and discharge is 4.45V vs. Li / Li + may be less than 4.4V vs. Li / Li + On the other hand, the lower limit of the positive electrode potential in the initial charge / discharge is not particularly limited, and may be, for example, 4.25 V vs. Li / Li + It may be over 4.3V vs. Li / Li + Or 4.35V vs. Li / Li + may be also possible.

[0127] Assembling a non-charged / discharged non-aqueous electrolyte storage element including a positive electrode, a negative electrode, and a non-aqueous electrolyte includes, for example, preparing an electrode body, preparing a non-aqueous electrolyte, and housing the electrode body and the non-aqueous electrolyte in a container. Preparing the electrode body includes preparing a positive electrode, preparing a negative electrode, and stacking or winding the positive electrode and the negative electrode with a separator interposed therebetween to form the electrode body.

[0128] The positive electrode can be prepared by applying a positive electrode mixture paste directly or via an intermediate layer to a positive electrode substrate and drying it. The positive electrode mixture paste contains each component constituting a positive electrode active material layer (positive electrode mixture), such as a positive electrode active material, and a dispersion medium. A suitable method for producing the positive electrode active material is as described above.

[0129] The negative electrode can be prepared, for example, by applying a negative electrode mixture paste directly or via an intermediate layer to a negative electrode substrate, and then drying the paste. The negative electrode mixture paste contains the components constituting the negative electrode active material layer (negative electrode mixture), such as the negative electrode active material, and a dispersion medium.

[0130] <Specific Configuration of Nonaqueous Electrolyte Energy Storage Element> The configuration of the nonaqueous electrolyte storage element according to the present invention is not particularly limited, and examples thereof include a cylindrical battery, a square battery (rectangular battery), and a flat battery. FIG. 1 shows a schematic diagram of a rectangular nonaqueous electrolyte storage element 1 (nonaqueous electrolyte secondary battery) which is an embodiment of the nonaqueous electrolyte storage element according to the present invention. The figure shows a perspective view of the inside of the container. In the nonaqueous electrolyte storage element 1 shown in FIG. 1, an electrode body 2 is housed in a container 3. The electrode body 2 is formed by winding a positive electrode having the positive electrode active material and a negative electrode having a negative electrode active material with a separator interposed therebetween. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode lead 41, and the negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode lead 51.

[0131] <Electricity storage device> The present invention can also be realized as an electricity storage device including a plurality of the nonaqueous electrolyte storage elements. FIG. 2 shows an embodiment of an electricity storage device according to an embodiment of the present invention. In FIG. 2, an electricity storage device 30 includes a plurality of electricity storage units 20. Each electricity storage unit 20 includes a plurality of nonaqueous electrolyte storage elements 1. At least one nonaqueous electrolyte storage element 1 included in the electricity storage device 30 may be a nonaqueous electrolyte storage element according to an embodiment of the present invention, and may include one nonaqueous electrolyte storage element according to an embodiment of the present invention and one or more nonaqueous electrolyte storage elements not according to an embodiment of the present invention, or may include two or more nonaqueous electrolyte storage elements according to an embodiment of the present invention. The electricity storage device 30 can be mounted as a power source for automobiles such as electric vehicles (EVs) and plug-in hybrid vehicles (PHEVs).

[0132] <Other embodiments> The present invention is not limited to the above-described embodiments, and various modifications may be made without departing from the scope of the present invention. For example, the configuration of one embodiment may be added to the configuration of another embodiment, and part of the configuration of one embodiment may be replaced with the configuration of another embodiment or a well-known technique. Furthermore, part of the configuration of one embodiment may be deleted. Also, a well-known technique may be added to the configuration of one embodiment.

[0133] In the above embodiment, the nonaqueous electrolyte storage element is mainly a nonaqueous electrolyte secondary battery, but the nonaqueous electrolyte storage element may be another type of nonaqueous electrolyte storage element, such as a capacitor (electric double layer capacitor, lithium ion capacitor, etc.). EXAMPLES

[0134] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0135] [No.1] (Preparation of hydroxide precursor) In preparing a positive electrode active material for a non-aqueous electrolyte storage element, a hydroxide precursor (positive electrode active material precursor) was prepared by reactive crystallization. First, 315.4 g of nickel sulfate hexahydrate, 168.6 g of cobalt sulfate heptahydrate, and 530.4 g of manganese sulfate pentahydrate were weighed out, and the total amount was dissolved in 4 L of ion-exchanged water to obtain a molar ratio of Ni:Co:Mn (X Ni :X Co :X Mn ) is 30:15:55, 1.0 mol / dm 3 In addition, 1.045 g of aluminum sulfate decahydrate was weighed out and the entire amount was dissolved in 0.4 L of ion-exchanged water to prepare an aqueous sulfate solution of 0.005 mol / dm 3 An aqueous aluminum sulfate solution of 1.0 mL was prepared. Next, 2 L of ion-exchanged water was poured into a reaction vessel having an internal volume of 5 L and an inner diameter of 170 mm, and oxygen contained in the ion-exchanged water was removed by bubbling nitrogen gas for 30 minutes. The temperature of the reaction vessel was set to 50°C (±2°C), and the reaction vessel was stirred at a rotation speed of 1500 rpm using a paddle blade equipped with a stirring motor, so that sufficient convection occurred in the reaction vessel. Next, the sulfate aqueous solution and the aluminum sulfate aqueous solution were dropped into the reaction vessel for 50 hours from separate nozzles separated by a distance of 50 mm to 100 mm at a rate of 1.3 mL / min and 0.13 mL / min, respectively. Here, the concentration of 4.0 mol / dm 3 of sodium hydroxide, 1.25 mol / dm 3 of ammonia, and 0.1 mol / dm 3The pH in the reaction tank was controlled to be always kept at 10.20 (±0.1) by appropriately dropping a mixed alkaline aqueous solution consisting of hydrazine and 100% hydrazine, and the total amount of the reaction liquid was controlled not to exceed 2 L by discharging a part of the reaction liquid by overflow. After the dropping was completed, stirring in the reaction tank was continued for another hour. After stirring was stopped, the mixture was left to stand at room temperature for 12 hours or more. Next, the hydroxide precursor particles generated in the reaction tank were separated using a suction filtration device, and sodium ions attached to the particles were washed and removed using ion-exchanged water, and the mixture was dried in an air atmosphere at normal pressure and 80°C for 20 hours using an electric furnace. After that, the mixture was ground in an automatic agate mortar for several minutes to make the particle size uniform. In this way, the molar ratio of Ni:Co:Mn (X Ni :X Co :X Mn ) is 30:15:55, and the molar ratio of Al:(Ni, Co, Mn) (X Al :X Me A hydroxide precursor was prepared with a 0.1:100 ratio of ZnO to hydroxide.

[0136] (Preparation of positive electrode active material) Lithium hydroxide monohydrate was added to the obtained hydroxide precursor and mixed thoroughly using an automatic agate mortar to obtain a molar ratio of Li:(Ni, Co, Mn) (X Ni :X Co :X Mn) was prepared. The mixed powder was pelletized, placed on an alumina boat, and heated from room temperature to 900°C over 10 hours in an air atmosphere under normal pressure using a box-type electric furnace (model number: AMF20), and fired at 900°C for 4 hours. After firing, the heater was turned off, and the alumina boat was left in the furnace and allowed to cool naturally. As a result, the temperature of the furnace dropped to about 200°C after 5 hours, but the temperature drop rate thereafter was somewhat slow. After a day and night, it was confirmed that the temperature of the furnace was 60°C or less, and then the pellets were taken out and crushed in an automatic agate mortar for several minutes to make the particle size uniform. In this way, the positive electrode active material according to No. 1 was produced. This positive electrode active material is in the form of particles, and a part of the aluminum is solid-dissolved in the lithium transition metal composite oxide, and another part of the aluminum is present on the surface of the lithium transition metal composite oxide particles.

[0137] [No.2 to No.5] Molar ratio of Al:(Ni, Co, Mn) (X Al :X Me Positive electrode active materials No. 2 to No. 5 were prepared in the same manner as No. 1, except that the amount of aluminum sulfate decahydrate was changed so that the average particle diameter (μm) of the positive electrode active materials was as shown in Table 1. These positive electrode active materials are in the form of particles, and a part of the aluminum is dissolved in the lithium transition metal composite oxide, and another part of the aluminum is present on the surface of the lithium transition metal composite oxide particles.

[0138] [No.6 to No.9] The molar ratio of Ni:Co:Mn (X Ni :X Co :X Mn Positive electrode active materials No. 6 to No. 9 were prepared in the same manner as No. 5, except that the amounts of nickel sulfate hexahydrate, cobalt sulfate heptahydrate, and manganese sulfate pentahydrate were changed so that the total weight of each positive electrode active material was as shown in Table 1. These positive electrode active materials are in the form of particles, and a part of the aluminum is dissolved in the lithium transition metal composite oxide, and another part of the aluminum is present on the surface of the lithium transition metal composite oxide particles.

[0139] [No.10, No.11] The molar ratio of Ni:Co:Mn (X Ni :X Co :X Mn The amounts of nickel sulfate hexahydrate, cobalt sulfate heptahydrate, and manganese sulfate pentahydrate were changed so that the Li:(Ni, Co, Mn) molar ratio (X Li :X Me Positive electrode active materials No. 10 and No. 11 were produced in the same manner as in No. 5, except that a mixed powder was prepared so that the ratio of aluminum to aluminum was 100:100. These positive electrode active materials are in the form of particles, and a part of the aluminum is dissolved in the lithium transition metal composite oxide, and another part of the aluminum is present on the surface of the lithium transition metal composite oxide particles.

[0140] [No.12] The molar ratio of Ni:Co:Mn (X Ni :X Co :X Mn The amounts of nickel sulfate hexahydrate, cobalt sulfate heptahydrate, and manganese sulfate pentahydrate were changed so that the Li:(Ni, Co, Mn) molar ratio (X Li :X Me A positive electrode active material according to No. 12 was produced in the same manner as in No. 5, except that a mixed powder was prepared so that the ratio of aluminum to aluminum was 140:100. This positive electrode active material was in the form of particles, and a part of the aluminum was dissolved in the lithium transition metal composite oxide, and another part of the aluminum was present on the surface of the lithium transition metal composite oxide particles.

[0141] [No.13] A lithium transition metal composite oxide was prepared in the same manner as in No. 1, except that the aluminum sulfate aqueous solution was not added dropwise during the preparation of the hydroxide precursor. This lithium transition metal composite oxide was used as the positive electrode active material of No. 13.

[0142] [No.14] First, a lithium transition metal composite oxide was prepared in the same manner as in No. 1, except that the aluminum sulfate aqueous solution was not added dropwise. -3mol / dm 3 The temperature of the aqueous solution in which aluminum citrate was dissolved in 200 mL of ion-exchanged water was kept at 50°C, and citric acid aqueous solution was added so that the pH was 2.75 to prepare an aqueous aluminum citrate solution. 5.0 g of the lithium transition metal composite oxide was immersed in this aqueous aluminum citrate solution, and after stirring at 600 rpm for 1 minute using a stirrer, the pH was adjusted to 7.0 to 7.5. At that time, if the pH was lower than the target value, an aqueous ammonia solution was added, and if it was higher, an aqueous citric acid solution was added. After adjusting the pH, the solution was stirred for another 5 minutes to precipitate Al-containing substances on the surface of the lithium transition metal composite oxide. Next, the lithium transition metal composite oxide particles were separated using a suction filtration device, and dried overnight at 80°C under normal pressure in an air atmosphere. The lithium transition metal composite oxide powder after the drying was placed on an alumina boat, and the temperature was raised from room temperature to 400°C at 5°C / min in an air atmosphere under normal pressure using a box-type electric furnace (model number: AMF20), and the powder was fired at 400°C for 8 hours. After the firing, the heater was turned off and the alumina boat was left in the furnace to cool naturally. After the furnace temperature was confirmed to be below 50°C, the boat was removed and crushed in an automatic agate mortar for several minutes to make the particle size uniform. In this way, the positive electrode active material according to No. 14 was produced. In this positive electrode active material, the surfaces of the lithium transition metal composite oxide particles are almost uniformly coated with aluminum oxide.

[0143] [No.15] A hydroxide precursor was prepared by reactive crystallization. First, 315.4 g of nickel sulfate hexahydrate, 168.6 g of cobalt sulfate heptahydrate, 530.4 g of manganese sulfate pentahydrate, and 20.89 g of aluminum sulfate decahydrate were weighed out, and the total amount was dissolved in 4 L of ion-exchanged water to obtain a molar ratio of Ni:Co:Mn (X Ni :X Co :X Mn ) is 30:15:55, and the molar ratio of Al:(Ni, Co, Mn) (X Al :X Me ) is 2:100, 1.0 mol / dm 3A sulfate aqueous solution of 4.0 mol / dm was prepared. Next, 2 L of ion-exchanged water was poured into a 5 L reaction vessel, and oxygen contained in the ion-exchanged water was removed by bubbling nitrogen gas for 30 minutes. The temperature of the reaction vessel was set to 50°C (±2°C), and the inside of the reaction vessel was stirred at a rotation speed of 1500 rpm using a paddle blade equipped with a stirring motor, so that sufficient convection occurred in the reaction vessel. Next, the above sulfate aqueous solution was dropped into the reaction vessel at a rate of 1.3 mL / min for 50 hours. Here, the concentration of 4.0 mol / dm 3 of sodium hydroxide, 1.25 mol / dm 3 of ammonia, and 0.1 mol / dm 3 The pH in the reaction vessel was controlled to be always kept at 10.20 (±0.1) by appropriately dropping a mixed alkaline aqueous solution consisting of hydrazine and 1.0% hydrazine, and the total amount of the reaction liquid was controlled not to exceed 2 L by discharging a part of the reaction liquid by overflow. After the dropping was completed, stirring in the reaction vessel was continued for another hour. After stopping the stirring, the mixture was left to stand at room temperature for 12 hours or more. The subsequent procedures were exactly the same as in No. 1, and the positive electrode active material according to No. 15 was produced. In this positive electrode active material, aluminum is completely dissolved in the lithium transition metal composite oxide.

[0144] [No.16, No.19] The molar ratio of Ni:Co:Mn (X Ni :X Co :X Mn The amounts of nickel sulfate hexahydrate, cobalt sulfate heptahydrate, and manganese sulfate pentahydrate were changed so that the Li:(Ni, Co, Mn) molar ratio (X Li :X Me Positive electrode active materials No. 16 and No. 19 were produced in the same manner as in No. 13, except that the mixed powder was prepared so that the ratio of the components (A, B, C, and C) was 100:100.

[0145] [No.17, No.20] The molar ratio of Ni:Co:Mn (X Ni :X Co :X MnThe amounts of nickel sulfate hexahydrate, cobalt sulfate heptahydrate, and manganese sulfate pentahydrate were changed so that the Li:(Ni, Co, Mn) molar ratio (X Li :X Me Positive electrode active materials Nos. 17 and 20 were produced in the same manner as in No. 14, except that the mixed powder was prepared so that the ratio of the aluminum oxide to the lithium transition metal composite oxide was 100:100. In these positive electrode active materials, the surfaces of the lithium transition metal composite oxide particles were almost uniformly coated with aluminum oxide.

[0146] [No.18, No.21] The molar ratio of Ni:Co:Mn (X Ni :X Co :X Mn The amounts of nickel sulfate hexahydrate, cobalt sulfate heptahydrate, and manganese sulfate pentahydrate were changed so that the Li:(Ni, Co, Mn) molar ratio (X Li :X Me Positive electrode active materials No. 18 and No. 21 were produced in the same manner as in No. 15, except that the mixed powder was prepared so that the ratio of the aluminum to the lithium transition metal composite oxide was 100:100. In these positive electrode active materials, aluminum was completely dissolved in the lithium transition metal composite oxide.

[0147] [No.22] A lithium transition metal composite oxide was prepared in the same manner as in No. 12, except that the aluminum sulfate aqueous solution was not added dropwise during the preparation of the hydroxide precursor. This lithium transition metal composite oxide was used as the positive electrode active material of No. 22.

[0148] <Preparation of positive electrode> For the positive electrode active materials No. 1 to No. 22, a positive electrode mixture paste was prepared containing the positive electrode active material, acetylene black (AB), and polyvinylidene fluoride (PVDF) in a ratio (solid content equivalent) of 90:5:5, and N-methylpyrrolidone (NMP) as a dispersion medium. This positive electrode mixture paste was applied to an aluminum foil (thickness 15 μm) as a positive electrode substrate, and dried to obtain a positive electrode.

[0149] <Preparation of negative electrode> A negative electrode mixture paste was prepared by mixing the negative electrode active materials graphite, styrene butadiene rubber (SBR), and carboxymethyl cellulose (CMC) in a ratio of 96:3.2:0.8 (solid content equivalent) and using water as a dispersion medium. This negative electrode mixture paste was applied to copper foil (thickness 10 μm) as a negative electrode substrate and dried to obtain a negative electrode.

[0150] <Test battery assembly> For each of No. 1 to No. 22, a test battery (non-aqueous electrolyte storage element) was assembled using the positive electrode and the negative electrode. The non-aqueous electrolyte was a non-aqueous solvent in which EC (ethylene carbonate), EMC (ethyl methyl carbonate), and dimethyl carbonate (DMC) were mixed in a volume ratio of 30:35:35, and lithium hexafluorophosphate (LiPF6) was added at a concentration of 1.0 mol / dm as an electrolyte salt. 3 A solution in which the content of each component was adjusted to the above range was used, and a polyolefin microporous film was used as the separator.

[0151] <Initial charge / discharge> The obtained nonaqueous electrolyte storage element before initial charging and discharging (non-charged and discharged nonaqueous electrolyte storage element) was subjected to initial charging and discharging at 25° C. in the following manner: charging current 0.1 C, charge cut-off voltage 4.25 V (positive electrode final potential 4.35 V vs. Li / Li + The battery was charged at a constant current and constant voltage of 0.1 C. The charge termination condition was the point at which the current value decayed to 0.02 C. Thereafter, the battery was discharged at a constant current of 0.1 C and a discharge termination voltage of 2.5 V.

[0152] <Oxygen position parameters> The oxygen location parameter was measured for the battery after the initial charge / discharge test using the above procedure and conditions. The obtained oxygen location parameter (zO1) is shown in Table 1.

[0153] Furthermore, the oxygen position parameters (zO1) of the positive electrode active materials No. 1 to No. 5, No. 10 to No. 12, No. 14, No. 15, No. 17, No. 18, No. 20, and No. 21 were calculated to determine the difference from the oxygen position parameters (zO2) measured under the same conditions for positive electrode active materials that do not contain aluminum and have the same molar ratio of transition metal elements. The oxygen position parameters (zO2) used were those of No. 13, No. 16, No. 19, and No. 22. The calculation results are shown in Table 1.

[0154] <High rate discharge performance test> For each nonaqueous electrolyte storage element after the initial charge / discharge test, a high-rate discharge performance test was performed by performing a total of two cycles of charge / discharge at 25°C in the following manner. Charging was performed at a constant current and constant voltage with a charge current of 1.0C and a charge cut-off voltage of 4.25V (positive electrode final potential 4.35V vs. Li / Li+), and the charge cut-off condition was the point when the current value decayed to 0.05C. Discharging was performed at a constant current with a discharge cut-off voltage of 2.5V. The discharge current was 0.1C in the first cycle and 5.0C in the second cycle. A rest period of 10 minutes was provided after each charge and discharge. The ratio of the 5.0C discharge capacity to the 0.1C discharge capacity in this charge / discharge test (5C / 0.1C discharge capacity ratio) was calculated. The results are shown in Table 1.

[0155] <Charge / discharge cycle capacity retention rate> After the above initial charge / discharge test, each nonaqueous electrolyte storage element was subjected to a charge / discharge cycle test at 45° C. in the following manner: charging current 1.0 C, charge cut-off voltage 4.25 V (positive electrode final potential 4.35 V vs. Li / Li + ) was charged at a constant current and constant voltage. The charge termination condition was the point when the current value decayed to 0.05C. Then, constant current discharge was performed with a discharge current of 1.0C and a discharge termination voltage of 2.5V. A 10-minute rest period was provided after each charge and discharge. This charge and discharge was repeated 100 times. The ratio of the discharge capacity after 100 cycles to the discharge capacity after 2 cycles in this charge and discharge cycle test was calculated as the charge and discharge cycle capacity retention rate [%]. The calculation results are shown in Table 1.

[0156] [Table 1]

[0157] As shown in Table 1, for the aluminum-containing positive electrode active materials, Nos. 1 to 5 and Nos. 10 to 12, in which the absolute value of the difference in oxygen position parameter between them and positive electrode active materials not containing aluminum and having the same composition in terms of the molar ratio of the transition metal elements is 0.002 or less, have superior 5C / 0.1C discharge capacity ratios and high charge / discharge cycle capacity retention rates compared to aluminum-containing positive electrode active materials in which the absolute value of the difference in oxygen position parameter exceeds 0.002.

[0158] In addition, as shown in Table 1, the nonaqueous electrolyte storage elements No. 1 to No. 11, which have an oxygen position parameter of 0.265 or more and 0.269 or less for the positive electrode active material containing aluminum, exhibit excellent values ​​for both the charge-discharge cycle capacity retention rate and the 5C / 0.1C discharge capacity ratio. Mn / X Me is 0.34 or more, and X Li / X Me The nonaqueous electrolyte storage elements No. 1 to No. 9 using a lithium transition metal composite oxide with a value of more than 1.0 as a positive electrode active material have an excellent charge / discharge cycle capacity retention rate of 92% or more.

[0159] In contrast, the nonaqueous electrolyte storage elements Nos. 13, 16, 19, and 22, which do not contain aluminum in the positive electrode active material, and Nos. 15, 18, and 21, which have an oxygen position parameter difference of -0.003, have low charge / discharge cycle capacity retention rates, and the nonaqueous electrolyte storage elements Nos. 14, 17, and 20, which have an oxygen position parameter difference of 0.003, have low 5C / 0.1C discharge capacity ratios. [Industrial Applicability]

[0160] The present invention can be applied to nonaqueous electrolyte storage elements used as power sources for electronic devices such as personal computers and communication terminals, automobiles, industrial devices, and the like. [Explanation of symbols]

[0161] 1. Non-aqueous electrolyte storage element 2 Electrode body 3 containers 4 Positive terminal 41 Positive lead 5 Negative terminal 51 Negative lead 20 Energy Storage Unit 30 Energy storage device

Claims

1. α-NaFeO 2 A positive electrode active material for a non-aqueous electrolyte storage element, comprising a lithium transition metal composite oxide having a structure: Further comprising aluminum, The lithium transition metal composite oxide contains at least one of nickel and cobalt, and manganese, the content of manganese in the transition metal in the lithium transition metal composite oxide is 0.6 or less in terms of molar ratio; Potential is 4.5V vs. Li / Li + Potential in the absence of any charging history of 4.35 V vs. Li / Li + a positive electrode active material for a nonaqueous electrolyte storage element, in which an oxygen position parameter of the positive electrode active material, which is determined by crystal structure analysis by the Rietveld method when the space group R3-m is used as a crystal structure model based on an X-ray diffraction pattern in a charged state of 0.265 or more and 0.269 or less.

2. α-NaFeO 2 A positive electrode active material for a non-aqueous electrolyte storage element, comprising a lithium transition metal composite oxide having a structure: Further comprising aluminum, The lithium transition metal composite oxide contains at least one of nickel and cobalt, and manganese, Potential is 4.5V vs. Li / Li + Potential in the absence of any charging history of 4.35 V vs. Li / Li + a positive electrode active material for a nonaqueous electrolyte storage element, in which the absolute value of the difference between an oxygen position parameter of the positive electrode active material obtained by crystal structure analysis by the Rietveld method when space group R3-m is used as a crystal structure model based on an X-ray diffraction pattern in a charged state of 0.002 or less and an oxygen position parameter obtained by the crystal structure analysis of a positive electrode active material which does not contain aluminum and has the same molar ratio of transition metal elements as the positive electrode active material.

3. 3. The positive electrode active material for a non-aqueous electrolyte storage element according to claim 2, wherein the content of manganese in the transition metal in the lithium transition metal composite oxide is 0.3 or more and 0.7 or less in terms of molar ratio.

4. 4. The positive electrode active material for a non-aqueous electrolyte storage element according to claim 1, wherein the ratio of the number of moles of lithium to the number of moles of transition metal in the lithium transition metal composite oxide is 1.0 or more and 1.4 or less.

5. 5. The positive electrode active material for a non-aqueous electrolyte storage element according to claim 1, wherein the ratio of the number of moles of aluminum to the number of moles of transition metal in the lithium transition metal composite oxide is 0.1 or more and 2 or less.

6. 6. The positive electrode active material for a nonaqueous electrolyte storage element according to claim 5, wherein the positive electrode active material is a particle containing the lithium transition metal composite oxide, and the ratio of the number of moles of aluminum to the sum of the number of moles of transition metal and the number of moles of aluminum is larger near the surface of the particle than near the center of the particle.

7. A positive electrode for a non-aqueous electrolyte storage element, comprising the positive electrode active material according to claim 1 .

8. A non-aqueous electrolyte storage element comprising the positive electrode for a non-aqueous electrolyte storage element according to claim 7 .

9. The positive electrode potential at the end of charge voltage during normal use is 4.5 V vs. Li / Li + The nonaqueous electrolyte storage element according to claim 8 , wherein the molecular weight is less than 1000.

10. 10. An electricity storage device comprising a plurality of nonaqueous electrolyte electricity storage elements, the electricity storage device comprising at least one of the nonaqueous electrolyte electricity storage elements according to claim 8 or 9.

11. Positive electrode potential is 4.5V vs. Li / Li + The method for using the nonaqueous electrolyte storage element according to claim 8 , further comprising charging the element within a range of less than 100%.

12. Positive electrode potential is 4.5V vs. Li / Li + The method for producing a nonaqueous electrolyte storage element according to claim 8 or 9, further comprising carrying out initial charging and discharging within a range of less than 100%.

Citation Information

Patent Citations

  • Positive electrode active material for lithium secondary battery and battery

    JP2002124261A

  • Positive electrode active material for lithium secondary battery, method of manufacturing positive electrode active material, electrode for lithium secondary battery, and lithium secondary battery

    JP2014063708A

  • Lithium secondary battery

    JP2016167446A

  • Positive electrode active material for non-aqueous electrolyte secondary battery, method for producing positive electrode active material for non-aqueous electrolyte secondary battery, positive electrode for non-aqueous electrolyte secondary battery, non-aqueous electrolyte secondary battery, method for producing non-aqueous electrolyte secondary battery, and method for use of non-aqueous electrolyte secondary battery

    WO2019244955A1